Analisis Komunikasi Pariwisata Digital pada Akun Instagram @explorebulukumba: Studi Kasus Promosi Pantai Bara Bulukumba - Henri; Nasir (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
The development of social media, especially Instagram, has changed the paradigm of tourism promotion through visual and interactive approaches. In the midst of the dominance of popular tourist destination promotions, community accounts such as @explorebulukumba play an important role in introducing little-known destinations, such as Bara Beach in Bulukumba Regency, South Sulawesi. This study aims to analyze the digital tourism communication strategy applied by the account in building the image of Bara Beach. The approach used was qualitative descriptive, with data collection through digital observation, semi-structured interviews, and field documentation. The research informants consisted of account managers, local tourism activists, and tourists who were exposed to digital promotional content. The results showed that @explorebulukumba accounts leveraged strong visual and narrative communication strategies through aesthetic content, the use of emotional captions, and local hashtags. These elements form the image of Bara Beach as an exclusive and natural destination. High user interaction shows the effectiveness of this strategy in attracting attention and encouraging tourist visit intentions. This research recommends collaboration between local governments and community accounts in digital tourism promotion strategies. In addition, increasing the capacity of creative content and optimizing social media features needs to be done on an ongoing basis to strengthen the branding of local destinations.